2015
DOI: 10.1007/s40477-014-0154-x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound (CEUS) versus computed tomography angiography (CTA) in detection of endoleaks in post-EVAR patients. Are delayed type II endoleaks being missed? A systematic review and meta-analysis

Abstract: The CEUS with its dynamic nature and longer scanning window demonstrated to be a highly sensitive modality for endoleak detection in comparison to CTA in delayed endoleaks type II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 38 publications
2
38
0
7
Order By: Relevance
“…Following the results of our work and the more recent literature [33], CEUS exam results are better than CT to identify endoleaks, since the relatively long time of permanence of the contrast agent (more than 5 min) in the blood flow and real-time study allows the study of patients also in delayed phases.…”
Section: Resultssupporting
confidence: 62%
“…Following the results of our work and the more recent literature [33], CEUS exam results are better than CT to identify endoleaks, since the relatively long time of permanence of the contrast agent (more than 5 min) in the blood flow and real-time study allows the study of patients also in delayed phases.…”
Section: Resultssupporting
confidence: 62%
“…CEUS has been shown to be as sensitive as CTA in detecting the type of endoleaks that would normally warrant an immediate intervention (types I and III) and can be more accurate in picking up slow endoleaks (type II) that CTA might miss or have difficulty detecting due to artefacts. [13][14][15] Minutes after contrast injection in CTA (the venous phase), the contrast density, within the aorta and an endoleak, is relatively low compared with the arterial phase. With CEUS, contrast resolution remains relatively high for a few minutes before significant depletion of contrast medium from cavitation or dissolution of microbubbles.…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al conducted a meta‐analysis and systematic review involving 454 patients to evaluate whether delayed EL‐II was detected during EVAR surveillance. The authors concluded that the dynamic nature of CEUS allowed better visualization of this type of endoleak than CTA.…”
Section: Discussionmentioning
confidence: 99%